Physical fitness components and bone health status of Malay male state level boxing, Muay Thai and silat athletes - Abidin, Muhammad Amrun Haziq (2018)
This study was carried out to determine the differences in physical fitness components and bone health status among Malay male state level boxing, Muay Thai and silat athletes. A total of 40 participants (mean age: 16.7 ± 1.5 years old) participated in this study. They were divided into four groups, i.e. sedentary control, boxing, Muay Thai and silat groups with 10 participants per group. Participants’ lung capacity, estimated maximal oxygen uptake (VO2max), anaerobic capacities, isokinetic muscular strength and power, hand grip strength, back and leg strength, standing long jump explosive power, Illinois agility, standing Stork balance and flexibility were measured. Bone sonometer was used to measure bone speed of sound (SOS) of participants’ tibia and radius dominant and non-dominant legs and arms. The main findings in the present study were that boxing athletes exhibited statistically significant (p<0.05) greater arm isokinetic muscular strength and power than silat athletes, and higher arm isokinetic muscular power than Muay Thai athletes. Boxing athletes also showed statistically significant (p<0.05) higher estimated VO2max compared to silat athletes. Comparison with the sedentary controls, boxing, Muay Thai and silat athletes showed statistically significant (p<0.05) greater Wingate mean power, and leg and arm isokinetic strength and power than sedentarycontrols. Boxing and Muay Thai athletes also showed statistically significant (p<0.01) greater estimated VO2max and jumping leg explosive power compared to sedentary controls. In addition, boxing athletes also exhibited statistically significant (p<0.01) greater hand grip strength of dominant and non-dominant hands than sedentary controls. Moreover, Muay Thai group exhibited statistically significant (p<0.05) greater radius bone SOS values of non-dominant arm compared to sedentary controls. In conclusion, this study found that boxing athletes exhibited greater arm isokinetic muscular strength and power than silat athletes, and also greater arm isokinetic muscular power than Muay Thai athletes. Boxing athletes also showed better aerobic fitness compared to silat athletes. Furthermore, involvement in boxing, Muay Thai and silat could enhance physical fitness components and bone health status of individuals compared to sedentary lifestyles. The findings obtained from this present study can be used as guidelines to facilitate the development of specific training programmes for boxing, Muay Thai and silat athletes, as well as promoting active lifestyle by engaging in martial arts such as boxing, Muay Thai and silat.